Parenteral nutritional support in surgical patients: expert consensus statements regarding intravenous lipid emulsions containing omega-3 fatty acids - Martindale, Robert G.; Evans, David C.; Waitzberg, Dan; Warren, Malissa; Mundi, Manpreet S.; Klek, Stanislaw; Wischmeyer, Paul E.; Rosenthal, Martin D. (Frontiers in Nutrition, 2025)
ObjectivesThe International Lipids in Parenteral Nutrition (PN) Summit was convened to offer practical guidance and expert consensus opinion regarding the use of intravenous lipid emulsions (ILEs) in various clinical settings. Herein, we briefly review aspects from this summit that are of particular importance for surgical/hospitalized patients.MethodsSummit participants identified and discussed new evidence, data, and analyses, that potentially influence the benefits and risks of ILEs in PN or their use in clinical practice. The summit meeting consisted of expert presentations that assessed recent clinical data and best practice, followed by periodic panel discussions to formulate consensus statements. Consensus statements were voted on, anonymously, by the meeting attendees.ResultsThis review briefly summarizes the rationale for considering ILE choice as a central component of any PN strategy for surgical/hospitalized patients. Thereafter, special patient populations are considered, such as surgery-related intestinal failure, major trauma, and those with chronic critical illnesses. Expert consensus statements are also provided to help bridge the gaps between evidence and clinical practice, hence complementing formal PN societal guideline recommendations.ConclusionThe choice of ILE in PN, particularly those containing fish oil, can play a vital role in improving outcomes for surgical patients.